IMPLEMENTASI METODE TA’WIDIYAH DALAM PENANAMAN NILAI-NILAI KARAKTER DI MADRASAH ALAM INSAN RABBANI KOTA SUNGAI PENUH - Habil, Muhammad; Samad, Duski; Nursyamsi (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the planning, implementation, and evaluation of the implementation of the ta'widiyah method in instilling character values in Madrasah Alam Insan Rabbani Kota Sungai TFull as a response to moral challenges in the era of globalization. The research method used is qualitative descriptive with a field research approach, where data is collected through observation, interviews, and documentation. The results of the study show that planning is carried out systematically by integrating religious values, discipline, honesty, independence, and environmental care into the madrasah culture. Its implementation is carried out consistently through worship routines, interaction with nature, and the example of teachers in a holistic and pressure-free learning atmosphere. Evaluation is carried out on an ongoing basis through direct observation of student behavior, daily reports, and joint reflection sessions. Despite facing challenges in the form of inconsistencies in parenting at home and the diversity of family backgrounds, the research concludes that a strong synergy between teachers, parents, and a supportive madrasah environment makes the ta'widiyah method very effective in shaping the personality and noble character of students as a whole.